2019
DOI: 10.1177/1362361319845563
|View full text |Cite
|
Sign up to set email alerts
|

Do minimally verbal and verbally fluent individuals with autism spectrum disorder differ in their viewing patterns of dynamic social scenes?

Abstract: Attending preferentially to social information in the environment is important in developing socio-communicative skills and language. Research using eye tracking to explore how individuals with autism spectrum disorder deploy visual attention has increased exponentially in the past decade; however, studies have typically not included minimally verbal participants. In this study, we compared 37 minimally verbal children and adolescents with autism spectrum disorder with 34 age-matched verbally fluent individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 73 publications
1
18
0
Order By: Relevance
“…Our findings indicated that individuals with ASD with a higher IQ appear to look less at heads and bodies specifically in the context in which shared focus was on the activity, suggesting that individuals with higher cognitive ability direct more attention to the focus of the actors’ gaze. This finding suggests caution regarding the specificity of head-looking across the heterogeneity of ASD and is consistent with other recent work demonstrating that children with ASD who are minimally verbal are less likely to follow gaze shifts relative to age-matched verbal children with ASD within a spontaneous looking task [ 60 ]. One possibility is that children with a higher IQ are more likely to share focus with other people, unlike children with lower IQ, which may ultimately impact opportunities for implicit social learning.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings indicated that individuals with ASD with a higher IQ appear to look less at heads and bodies specifically in the context in which shared focus was on the activity, suggesting that individuals with higher cognitive ability direct more attention to the focus of the actors’ gaze. This finding suggests caution regarding the specificity of head-looking across the heterogeneity of ASD and is consistent with other recent work demonstrating that children with ASD who are minimally verbal are less likely to follow gaze shifts relative to age-matched verbal children with ASD within a spontaneous looking task [ 60 ]. One possibility is that children with a higher IQ are more likely to share focus with other people, unlike children with lower IQ, which may ultimately impact opportunities for implicit social learning.…”
Section: Discussionsupporting
confidence: 89%
“…To account for within-participant variability in % Valid Time, the model included a participant identifier as the random intercept. The model was fit by using the R package "nlme" (Pinheiro et al, 2018) and maximizing the restricted log-likelihood function. Significance of the fixed effects was assessed using the analysis of variance type III sum of squares and the Wald χ 2 test (Supplementary Table 2), as implemented in the R package "car" (Fox & Weisberg, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond characterizing the lexical profile of PV-MV children with ASD, we tested whether the observed differences could be attributed to social weaknesses that are characteristic of ASD. The lower proportion of people words could be related to lower rates of social orienting and reduced attention to people’s faces that have been identified in children with ASD and specifically minimally verbal children with ASD (Dawson et al, 2004; Plesa Skwerer et al, 2019). Our word-level data also provide extra detail to the reduced proportion of people words that we identified.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, early social abilities may link to later language abilities. A recent study tracked eye-gaze patterns 8 CHARACTERIZING MINIMALLY VERBAL ASD LEXICONS of minimally verbal and verbally fluent children with ASD while they viewed social scenes and found minimally verbal children with ASD spent less time looking at faces at critical moments that provided insight into the actor's behaviors (Plesa Skwerer et al, 2019). The study also found that, during a social scene with an adult, a moving object, and static object, minimally verbal children spent a similar amount of time looking at the moving object, but verbally fluent children spent more time looking at the adult's face.…”
Section: Social Attentionmentioning
confidence: 99%
See 1 more Smart Citation